1998
DOI: 10.1093/brain/121.1.47
|View full text |Cite
|
Sign up to set email alerts
|

A neuromodulatory role for the human amygdala in processing emotional facial expressions

Abstract: Localized amygdalar lesions in humans produce deficits in the recognition of fearful facial expressions. We used functional neuroimaging to test two hypotheses: (i) that the amygdala and some of its functionally connected structures mediate specific neural responses to fearful expressions; (ii) that the early visual processing of emotional faces can be influenced by amygdalar activity. Normal subjects were scanned using PET while they performed a gender discrimination task involving static grey-scale images of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

86
725
11
16

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,143 publications
(838 citation statements)
references
References 67 publications
86
725
11
16
Order By: Relevance
“…cingulate, amygdala) associated with attention and/or motivation, indexing adaptive signi®cance (Lang et al, 1998). A direct test of this hypothesis con®rmed a modulatory role of the amygdala for brain activity in the extrastriate cortex (Morris et al, 1998). Similar reentrant processing linked to affect-related personality features might have been active in the present paradigm.…”
Section: Functional Signi®cance Of the Personality-modulated Microstatesmentioning
confidence: 54%
See 1 more Smart Citation
“…cingulate, amygdala) associated with attention and/or motivation, indexing adaptive signi®cance (Lang et al, 1998). A direct test of this hypothesis con®rmed a modulatory role of the amygdala for brain activity in the extrastriate cortex (Morris et al, 1998). Similar reentrant processing linked to affect-related personality features might have been active in the present paradigm.…”
Section: Functional Signi®cance Of the Personality-modulated Microstatesmentioning
confidence: 54%
“…PET and fMRI studies using visual stimuli demonstrated activation of primary and secondary visual areas during emotional processing (Lane et al, 1997;Lang et al, 1998;Morris et al, 1998;Nakamura et al, 1998). This was accounted for by reentrant processes from more anterior structures (e.g.…”
Section: Functional Signi®cance Of the Personality-modulated Microstatesmentioning
confidence: 99%
“…However, there is some debate on how such rapid perception is accomplished. A fast subcortical thalamus‐amygdala route bypassing the visual cortex is thought to transmit coarse face‐related information (LeDoux, 2009; Morris et al, 1998), but its role in face perception is controversial (Krolak‐Salmon et al, 2004; Pessoa & Adolphs, 2011), including whether it is fear‐specific (Méndez‐Bértolo et al, 2016) or non‐specific to expression (Garvert, Friston, Dolan, & Garrido, 2014; McFadyen et al, 2017). On the other hand, multiple fast cortical pathways forming part of a feedforward and feedback mechanism consistute an equally plausible mechanism for rapid expression perception (Liu & Ioannides, 2010; Pessoa & Adolphs, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Both lesion and functional-imaging studies in humans have demonstrated the amygdala's role in the visual recognition of emotional facial expressions (1)(2)(3). Studies in humans further indicate the amygdala's participation in assessing the significance of paralinguistic emotional stimuli (1,4).…”
mentioning
confidence: 98%